Evaluasi Kondisi Lingkungan Fisik Kerja Dan Heat Stress dengan WBGT Index Pada Stasiun Casting - Fathurochman, Tri Rizqi; Sarvia, Elty (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2021)
Hot and noisy physical environment can cause heat stress for the operator, one example is heat exhaustion such as symptoms of dizziness or headaches. This research aims to improve physical environmental conditions so that it provide a better, convenient, and support to work activities. The results of the analysis showed that the current condition has not fulfilled the standard of lighting in accordance to Kepmenkes RI No. 1405 year 2002, has not fulfilled the standards of Kepmenkes RI No. 1405 year 2002 about the condition of noise, has not fulfilled the standard of Kepkemenakertrans Per. 13MEN/X/2011 regarding temperature conditions using WBGT. The temperature and humidity conditions are far from the optimal point on the psychometric chart according to AYAF (The Australian Institute of Refrigeration Air Conditioning and Heating) 2007. Air circulation is also not good and there is a smell of lead combustion. Therefore, there is a need for the addition of 20 lamps to illuminate the casting station, the use of ear plugs to reduce noise, the use of two evaporative cooling and four pieces of exhaust fan to reduce heat by calculation of heat reduction according to ASHRAE, 2007. Temperature drops as much as 7.68 ° C, approaching the optimal point is 25 ° C with humidity 80% if the company will use evaporative cooling. In addition, it is proposed to mount the walls surrounding the casting station to avoid heat spread to other stations with a hole underneath it for cool air inlet spilled out by evaporative cooling.